2006
DOI: 10.1002/cncr.21695
|View full text |Cite
|
Sign up to set email alerts
|

First‐ and second‐line chemotherapy with docetaxel or mitoxantrone in patients with hormone‐refractory prostate cancer

Abstract: BACKGROUNDDocetaxel and mitoxantrone are considered first‐line chemotherapeutic options in patients with hormone‐refractory prostate cancer (HRPC), but their clinical effectiveness in a second‐line setting is unknown. Therefore, the authors conducted a population‐based retrospective study to establish activity and tolerability of second‐line docetaxel or mitoxantrone in HRPC.METHODSThe study included 68 patients who had failed androgen ablation therapy and who received docetaxel and mitoxantrone in either sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…12 The timing of docetaxel therapy in men with evidence of metastases, but without symptoms, should be discussed with patients and therapy should be individualized based on patients' clinical status and preferences (Level 3, Grade C).…”
Section: First-line Systemic Chemotherapymentioning
confidence: 99%
“…12 The timing of docetaxel therapy in men with evidence of metastases, but without symptoms, should be discussed with patients and therapy should be individualized based on patients' clinical status and preferences (Level 3, Grade C).…”
Section: First-line Systemic Chemotherapymentioning
confidence: 99%
“…Moreover, 46% of patients in the mitoxantrone-after-docetaxel group and 64% patients in the docetaxel-after-mitoxantrone group had to have dose reduction, delay or cessation of chemotherapy or hospitalization as a result of toxicity. [34] Other studies confirmed the activity of taxane-based chemotherapy before or after mitoxantrone but the duration of responses is short and there is no difference in OS or PFS regardless of the drug sequence used. [35]…”
Section: Second-line Treatments For Hrpcmentioning
confidence: 99%
“…[33] The largest of crossover trials comparing docetaxel and mitoxantrone as second-line agents was published by Michels et al . [34] These authors found that second-line docetaxel after first-line mitoxantrone-based chemotherapy produced better PSA responses than second-line mitoxantrone after docetaxel. Despite the PSA responses, neither of these strategies improved PFS or OS, which were two to three months and seven to 12 months, respectively.…”
Section: Second-line Treatments For Hrpcmentioning
confidence: 99%
“…These treatments include second generation androgen receptor blockers, inhibition of androgen biosynthesis with an agent such as abiraterone (6), and taxane chemotherapy with docetaxel or cabazitaxel (7). There have been studies using mitoxantrone but multiple studies have shown increased toxicity with response rates between 9-20% (7)(8)(9)(10). Radium 223 is also approved for use in castrate resistant prostate cancer with bone metastases (11).…”
Section: Introductionmentioning
confidence: 99%